Multi-sensor calibration and multi-modal perception for intelligent systems - Zhang, Jun (Nanyang Technological University, 2022)
Nowadays, various intelligent systems rely on multiple heterogeneous sensors for environmental perception. For example, different sensors are mounted on unmanned vehicles, autonomous mobile robots and to the road side. By fusing heterogeneous sensors, the perception system could be more robust in complex real environments. To achieve that, accurate extrinsic calibration is indispensable, through which the transformation matrix (rotation matrix and translation vector) between the sensor frames can be obtained. However, as new sensors enter the market and new applications arise, new problems need to be solved. In this thesis, a bunch of solutions are proposed for different scenarios.